Valuing Access to Water : A Spatial Hedonic Approach Applied to Indian Cities - Anselin, Luc (Washington, DC: World Bank, 2012)
An important infrastructure policy issue for rapidly growing cities in developing countries is how to raise fiscal revenues to finance basic services in a fair and efficient manner. This paper applies hedonic analysis that explicitly accounts for spatial spillovers to derive the value of improved access to water in the Indian cities of Bhopal and Bangalore. The findings suggest that by looking at individual or private benefits only, the analysis may underestimate the overall social welfare from investing in service supply especially among the poorest residents. The paper further demonstrates how policy simulations based on these estimates help prioritize spatial targeting of interventions according to efficiency and equity criteria.